CD47 Blockade and Cowpea Mosaic Virus Nanoparticle in situ Vaccination Synergistically Triggers Phagocytosis and Tumor Killing - Wang, Chao. (Adv Healthc Mater, 2019)
Contemporary immunotherapies, e.g. those that target the CTLA-4 and PD-1/PD-L1 axis, act on T cells to reinstate their antitumor activity. An alternative, and possibly more powerful approach is to target and reprogram the innate immune system within the tumor microenvironment. To this end, blockade of CD47 has been demonstrated as an attractive approach. Blockade of CD47 inhibits antiphagocytic signals therefore inducing macrophage phagocytosis of cancer cells. CD47 blockade also primes antitumor T-cell responses by either activating antigen presenting cells or inhibiting interactions between CD47 on cancer cells and the matricellular protein thrombospondin-1 (TSP1) on T cells. Here, we identified a combination immunotherapy using cowpea mosaic virus (CPMV) in situ vaccination and CD47-blocking antibodies. The CPMV in situ vaccine synergizes with CD47 blockade, because CPMV in situ vaccination activates the innate immune system, leading to recruitment and activation of phagocytes. Therefore, the combination therapy targets monocytes and boosts their ability of cancer cell phagocytosis, in turn priming the adaptive immune system leading to a potent antitumor immune response. This work presents a novel strategy to promote macrophage activity to kill tumor cells, and hold promise to enhance T cells targeted immunotherapies by inducing both innate and adaptive arms of immune system.